Is balance performance reduced after mild traumatic brain injury?: Interim analysis from chronic effects of neurotrauma consortium (CENC) multi-centre study. (24th August 2018) - Walker, William C.; Nowak, Kayla J.; Kenney, Kimbra; Franke, Laura Manning; Eapen, Blessen C.; Skop, Karen; Levin, Harvey; Agyemang, Amma A.; Tate, David F.; Wilde, Elisabeth A.; Hinds, Sidney; Nolen, Tracy L.
ABSTRACT: Objectives : Determine if mild traumatic brain injury (mTBI) history is associated with balance disturbances. Setting : Chronic Effects of Neurotrauma Consortium (CENC) centres. Participants : The CENC multi-centre study enrols post-9/11 era Service Members and Veterans with combat exposure. This sample ( n  = 322) consisted of enrolees completing initial evaluation by September 2016 at the three sites conducting computerized dynamic post-urography (CDP) testing. Design : Observational study with cross-sectional analyses using structural equation modelling. Main Measures : Comprehensive structured interviews were used to diagnose all lifetime mild traumatic brain injuries (mTBIs). The outcome, Sensory Organization Test (SOT), was measured on CDP dual-plate force platform. Other studied variables were measured by structured interviews, record review and questionnaires. Results : The overall positive/negative mTBI classification did not have a significant effect on the composite equilibrium score. However, the repetitive mTBI classification showed lower scores for participants with ≥ 3 mTBI versus 1–2 lifetime mTBIs. For repetitive mTBI, pain interference acted as a mediator for the indirect effect, and a direct effect was evident on some sensory condition equilibrium scores. Conclusion : These findings show that repeated mTBI, partially mediated by pain, may lead to later balance disturbances among military combatants. Further study of CDP outcomes within this accruing cohort is warranted.